Test Case Generation Model for UML Diagrams - Dawood Salman, Yasir; Hashim, Nor Laily (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
The complexity and size of software have been sequentially increasing, and the scope of testing is expanding. To insure deadline delivery and decrease development test cost, the efficiency of software testing needs to be improved. Several approaches for automated test case generation have been proposed over the last few years. However, models for automated test case generation for unified modeling language (UML) diagrams are still in the early stage of development. UML is the most widely used language to describe software analysis and design. Given that test cases can be efficiently derived from UML models, the generation of test cases from UML diagrams has attracted increasing research attention. However, no model currently exists for mapping the generation procedure. This paper proposes a model for automatic test case generation from UML diagrams.